Saaraahka – in Njaarke during the 1720s - Rydving, Håkan (Sámi dieđalaš áigečála, 2024)
When previous researchers have examined the functions of the goddess Saaraahka, they have based their studies on all the available material about her, from all areas of Saemien eatneme / Saepmie and at all time periods. The picture they created of her was therefore a mixture of things that never coexisted, neither in any area, nor during any time period. In addition, most previous researchers erroneously regarded Saaraahka as less important than the male divinities. In this article I have tried instead to focus on what the sources from a certain area (Njaarke in northern Trøndelag, Norway) and a specific time period (the 1720s) tell us about Saaraahka. By means of a critical investigation targeting relevant earlier sources, this article shows how important Saaraahka was in daily life in Njaarke in the 1720s. Saaraahka helped women during menstruation, pregnancy, and childbirth, and one therefore sacrificed both animals and objects to her. Saaraahka was, however, important for both men and women. Every day one performed rituals to her when one ate. Naming rituals were performed in her name, and one performed a ritual to her before or after being forced to partake of Holy Communion in church. In Njaarke during the 1720s, Saaraahka was in fact the most important of all the invisible beings.